Assessment of Air Quality Using the Plume Air Quality Index Indicator (PAQI): Reference to Five Towns in Nigeria - Abulude, Francis Olawale; Acha, Sunday; Adamu, Ademola Samuel; Araifalo, Kikelomo Mabinuola; Kenni, Amoke Monisola; Bello, Lateef Johnson; Gbotoso, Arinola Oluwatoyin (ASEAN Journal of Science and Engineering, 2023)
Air quality is an important issue worldwide due to the health implications on man and livestock. For this reason, different countries constructed the air quality index (AQI) which depicts pollution levels and the impact on health. PAQI is an example of an air quality index built by Plume Labs, Paris, France. It has seven levels (Low, Moderate, High, Very High, Excessive, Extreme, and Airpocalypse) of pollution which are linked to the World Health Organization (WHO) limits. This study aimed to assess the AQI of five different towns in Nigeria using the satellite model data released by Plumes Labs. Daily data of the towns were recorded between 9 am and 7 pm for 60 days and statistically analyzed. The air quality index was determined by whatever pollutant was measuring the highest. It was observed that PM2.5 and 03 (30 and 40 respectively) had the highest concentration levels most times. The results were compared with the PAQI indicator. The air quality of the towns has reached high levels of pollution above the maximum limit for 24 hours established by WHO.